2022
DOI: 10.3390/foods11233777
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Analysis Reveal Multiple Strategies for the Cadmium Tolerance in Vibrio parahaemolyticus N10-18 Isolated from Aquatic Animal Ostrea gigas Thunberg

Abstract: The waterborne Vibrio parahaemolyticus can cause acute gastroenteritis, wound infection, and septicemia in humans. Pollution of heavy metals in aquatic environments is proposed to link high incidence of the multidrug-resistant (MDR) pathogen. Nevertheless, the genome evolution and heavy metal tolerance mechanism of V. parahaemolyticus in aquatic animals remain to be largely unveiled. Here, we overcome the limitation by characterizing an MDR V. parahaemolyticus N10-18 isolate with high cadmium (Cd) tolerance us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 105 publications
2
11
0
Order By: Relevance
“…In this study, our results revealed that the cytoplasma membrane permeability of V. cholerae J9-62 and Q6-10 isolates was significantly increased under the Pb 2+ (200 μg/mL), and Cd 2+ (12.5 μg/ mL) or Zn 2+ (50 μg/mL) stresses, respectively (p < 0.05). The increased inner membrane permeability was also found in V. parahaemolyticus N10-8 after treated with a sublethal concentration of Cd 2+ (50 μg/mL) in our recent study (Yu P. et al, 2022). Likewise, cell membrane fluidity affected most compounds and ions (such as nutrients and heavy metals) to cross the bacterial cytoplasma membrane (Bessa et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…In this study, our results revealed that the cytoplasma membrane permeability of V. cholerae J9-62 and Q6-10 isolates was significantly increased under the Pb 2+ (200 μg/mL), and Cd 2+ (12.5 μg/ mL) or Zn 2+ (50 μg/mL) stresses, respectively (p < 0.05). The increased inner membrane permeability was also found in V. parahaemolyticus N10-8 after treated with a sublethal concentration of Cd 2+ (50 μg/mL) in our recent study (Yu P. et al, 2022). Likewise, cell membrane fluidity affected most compounds and ions (such as nutrients and heavy metals) to cross the bacterial cytoplasma membrane (Bessa et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Changes in cell biophysical properties have been disclosed as stressors affecting compound and ion transport and cell integrity (Yu P. et al, 2022). Bacterial strains applied different mechanisms to response to heavy metals, such as bond formation between bacterial cell surface and metal ions to decrease their toxicity (Heidari and Panico, 2020;Wróbel et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations